Human Umbilical Cord Blood-Derived CD34+Cells Can Be Used as a Prophylactic Agent for Experimental Heatstroke - Wei-Shou Hwang; Sheng-Hsien Chen; Cheng-Hsien Lin; Hsiu-Kang Chang; Wei-Chun Chen; Mao-Tsun Lin (Elsevier, 2008)
We attempted to assess the prophylactic effect of human umbilical cord blood-derived CD34+cells in experimental heatstroke. Anesthetized rats, 1 day before heat stress, were divided into 2 major groups and given CD34−cells (defined by 1 × 106human cord blood lymphocytes and monocytes that contained <0.2% CD34+cells) or CD34+cells (defined by 1 × 106human cord blood lymphocytes and monocytes that contained >95% CD34+cells). They were exposed to ambient temperature of 43°C for 70 min to induce heatstroke. When the CD34−cells-treated or untreated rats underwent heat stress, their survival time values were found to be 20 -24 min. Pretreatment with CD34+cells significantly increased survival time (123 -351 min). As compared with normothermic controls, all CD34−cells-treated heatstroke animals displayed hypotension, hepatic and renal failure, hypercoagulable state, activated inflammation, and cerebral ischemia and injury. However, these heatstroke reactions all were significantly suppressed by CD34+cells pretreatment. In addition, the levels of interlukin-10 in plasma and glial cell line-derived neurotrophic factors in brain were all significantly increased after CD34+cell administration during heatstroke. Our data indicate that human umbilical cord-derived CD34+cells can be used as a prophylactic agent for experimental heatstroke. Keywords:: heatstroke, CD34+cell, cytokine, multiorgan dysfunction, coagulation